Mode I Stress Intensity Factors for triangular corner crack nearby intersecting of cylindrical holes - E. Salvati; P. Livieri; R. Tovo (Fracture and Structural Integrity)
In this paper triangular flaws has been taken into account at the intersection of two holes inside a specified specimen. Influence of bore hole D1/D2 and angle between their axes α are examined. Numerical analysis are performed to determine Stress Intensity factors (SIF) in many geometric configurations. Afterwards, fitting weight function’s parameters with FEM results, new SIF analytics expression are shown. Finally, the accuracy of weight functions in SIF predictions for different inner pressure, has been checked as well as the comparison between the SIF of a triangular crack and that of an actual crack shape obtained through a fatigue test.